E-health/m-health adoption and lifestyle improvements: Exploring the roles of technology readiness, the expectation-confirmation model, and health-related information activities. (July 2019) - Leung, Louis; Chen, Cheng
Abstract: This purpose of this study was to investigate (a) the prevalence and patterns of e-health/m-health use in Hong Kong; (b) the activities that people engage in via health-related information platforms/apps; and (c) the roles that technology readiness, the expectation-confirmation model, and e-health/m-health activities play in predicting lifestyle improvement. Data were collected from a telephone survey, with a probability sample of 1, 007 respondents aged 18 or above. Our results show that 47.2% of the respondents were regular users of e-health technologies, 23.2% were m-health users, and only 10.7% used wearables for health purposes. Among the six e-health/m-health activities identified, health tutorials and health information seeking were the most frequently used, followed by recording/monitoring and medical services. The least popular activities were reminders and sharing experiences. As expected, the component variables in the expectation-confirmation model, particularly confirmation and perceived usefulness, were the strongest predictors for lifestyle improvement. External factors, such as being older and innovative, the use of e-health/m-health activities for recording/monitoring, health tutorials, medical services, and sharing experiences, also had significant impacts. Theoretical and practical implications are discussed. Highlights: Explored how technology readiness, the ECM model, and e-health/m-health activities affect lifestyle improvement. 47.2% of the respondents were regular users of e-health technologies, 23.2% m-health users, and only 10.7% used wearables. Identified six e-health/m-health activities (e.g., information seeking, medical services, and sharing experiences). Confirmation, perceived usefulness, being older, and innovative were the strongest predictors for lifestyle improvement.